2021
DOI: 10.3390/s21165294
|View full text |Cite
|
Sign up to set email alerts
|

Automated Bowel Sound Analysis: An Overview

Abstract: Despite technological progress, we lack a consensus on the method of conducting automated bowel sound (BS) analysis and, consequently, BS tools have not become available to doctors. We aimed to briefly review the literature on BS recording and analysis, with an emphasis on the broad range of analytical approaches. Scientific journals and conference materials were researched with a specific set of terms (Scopus, MEDLINE, IEEE) to find reports on BS. The research articles identified were analyzed in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…Recent increases in computer processing power and improvements in data analysis bring the potential to employ bowel sound computational analysis to improve evaluation of gastrointestinal conditions [2] or feeding status [3,4]. A number of computerized bowel sound-based monitoring and diagnosis systems have been developed [5,6]. The development stage of the various technologies varies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent increases in computer processing power and improvements in data analysis bring the potential to employ bowel sound computational analysis to improve evaluation of gastrointestinal conditions [2] or feeding status [3,4]. A number of computerized bowel sound-based monitoring and diagnosis systems have been developed [5,6]. The development stage of the various technologies varies.…”
mentioning
confidence: 99%
“…Improved accuracy at this stage will improve to the accuracy of any subsequent signal processing or analysis. A recent overview of automatic bowel sound analysis methods, also suggested that the detection of the BS occurrence could be a starting point for building bowel sound analysis standards, as well as international forums for discussion and cooperation [6].…”
mentioning
confidence: 99%
“…In addition, we can also determine the recovery of the intestinal tract by monitoring bowel sounds, because bowel sounds are produced by the peristaltic movement of the intestinal tract to push the intestinal contents and cause the intestinal contents to hit each other or the intestinal contents to collide with the intestinal wall, which can reect the intestinal movement. 13,14 Currently, clinical auscultation of bowel sounds is mainly performed with a stethoscope, but the judgment of the results depends on the physician's level of experience, and diagnostic errors can occur. 15 Moreover, studies have shown that the correct rate of clinician auscultation of bowel sounds is less than 90%.…”
Section: Introductionmentioning
confidence: 99%
“…They have not only proposed their own neural network-based approach to BS identification, but also studied irritable bowel syndrome and demonstrated a link between BS and migrating motor complexes in the large bowel [14]. For more historical context we refer to our recent review [15].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning methods are widely used in bowel sound analysis [15]. One solution using machine learning algorithms is the use of the parameters Jitter and Shimmer, i.e., parameters that determine the variation of the fundamental frequency in relation to the frequency of the fundamental tone and the variation of the amplitude in relation to the average amplitude.…”
Section: Introductionmentioning
confidence: 99%